2023
DOI: 10.3389/fgene.2023.1227724
|View full text |Cite
|
Sign up to set email alerts
|

When NIPT meets WES, prenatal diagnosticians face the dilemma: genetic etiological analysis of 2,328 cases of NT thickening and follow-up of pregnancy outcomes

Abstract: Objective: To assess the performance of diverse prenatal diagnostic approaches for nuchal translucency (NT) thickening and to investigate the optimal prenatal screening or diagnostic action with a NT thickening of 95th percentile-3.50 mm.Methods: A retrospective analysis of 2,328 pregnancies with NT ≥ 95th percentile through ultrasound-guided transabdominal chorionic villus sampling (CVS), amniocentesis, or cordocentesis obtained clinical samples (chorionic villi, amniotic fluid, and cord blood), and real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…CMA has higher resolution than conventional karyotyping, allowing the detection of smaller, submicroscopic imbalances, even some cases of uniparental disomy (i.e., involving isodisomy), by SNP array [ 19 ]. Therefore, our data also suggested that CMA may have an additional value in chromosome diagnosis not only in fetuses with NT ≥ 3.5 mm, but in fetuses with NT 3.0–3.4 mm as well, which was agreed with previous studies [ 14 , 20 23 ]. Except routine screening for aneuploids, any pregnancy whose goal is to maximize the diagnostic yield of chromosome aberrations in their pregnancy should be offered prenatal diagnosis with microarray.…”
Section: Discussionsupporting
confidence: 93%
“…CMA has higher resolution than conventional karyotyping, allowing the detection of smaller, submicroscopic imbalances, even some cases of uniparental disomy (i.e., involving isodisomy), by SNP array [ 19 ]. Therefore, our data also suggested that CMA may have an additional value in chromosome diagnosis not only in fetuses with NT ≥ 3.5 mm, but in fetuses with NT 3.0–3.4 mm as well, which was agreed with previous studies [ 14 , 20 23 ]. Except routine screening for aneuploids, any pregnancy whose goal is to maximize the diagnostic yield of chromosome aberrations in their pregnancy should be offered prenatal diagnosis with microarray.…”
Section: Discussionsupporting
confidence: 93%